Implementasi Sistem Pengelolaan Data Semen Beku Ternak di Balai Inseminasi Buatan Provinsi Kalimantan Selatan - Budi Rahmani; Adinda Dewi Puspa Rini; Awenta Defari Mahan (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2024)
This activity aims to primarily implement a web-based information system in the Production & Distribution section of the Artificial Insemination Center of South Kalimantan Province. Administrative tasks include producing, storing, and distributing frozen livestock semen. The hope for this implementation is efficiency, speed, and accuracy in managing production data, distribution, bull data, straw culling data, and frozen semen stock data. The method involves developing web-based software that can process data in real-time, allowing operators to input information directly in the field. Implementation processes include user training and testing to ensure system success. The results of this dedication include transforming manual administrative systems into digital ones, facilitating faster and more accurate data input. The generated reports on production information, distribution, bull data, straw culling data, and frozen semen stock can meet the standards of this center. The impact of this activity is evident in the increased operational efficiency and information accuracy. Information technology is expected to enhance the Artificial Insemination Center's competitiveness in the era of globalization. This dedication has the potential for long-term positive impact, not only at the institutional level but also in supporting the broader development of the livestock sector. The practical implementation of information technology is hoped to serve as an example for similar institutions in their efforts to improve operational efficiency and effectiveness.